Partner-based adherence intervention for second-line antiretroviral therapy (ACTG A5234): a multinational randomised trial. - Gross, Robert; Zheng, Lu; Rosa, Alberto La; Sun, Xin; Rosenkranz, Susan L; Cardoso, Sandra Wagner; Ssali, Francis; Camp, Rob; Godfrey, Catherine; Cohn, Susan E; Robbins, Gregory K; Chisada, Anthony; et al. (The lancet. HIV, 2015)
Adherence is key to the success of antiretroviral therapy. Enhanced partner support might benefit patients with previous treatment failure. We aimed to assess whether an enhanced partner-based support intervention with modified directly observed therapy would improve outcomes with second-line therapy in HIV-infected patients for whom first-line therapy had failed.